2014
DOI: 10.1159/000366335
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Hyperplasia inGasp-1Overexpressing Mice is Dependent on Myostatin Up-Regulation

Abstract: Background/Aims: Overexpression of Gasp-1, an inhibitor of myostatin, leads to a hypermuscular phenotype due to hypertrophy rather than hyperplasia in mice. However to date, the cellular and molecular mechanisms underlying this phenotype are not investigated. Methods: Skeletal muscles of overexpressing Gasp-1 mice, called Tg(Gasp-1) mice, were analyzed by histological methods. Satellite cell-derived myoblasts from these mice were used to investigate the molecular mechanisms. Results: We demonstrated that hyper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 51 publications
1
18
1
Order By: Relevance
“…Our previous molecular analysis performed on young Tg(Gasp-1) mice revealed an increase of myostatin expression responsible for the absence of hyperplasia [31]. We hypothesized that this upregulation of myostatin could also be implicated in the insulin resistance phenotype observed in old mutant mice.…”
Section: Resultsmentioning
confidence: 91%
See 4 more Smart Citations
“…Our previous molecular analysis performed on young Tg(Gasp-1) mice revealed an increase of myostatin expression responsible for the absence of hyperplasia [31]. We hypothesized that this upregulation of myostatin could also be implicated in the insulin resistance phenotype observed in old mutant mice.…”
Section: Resultsmentioning
confidence: 91%
“…Recent studies have shown that Mstn -/- mice leads to an increase of insulin sensitivity, a decrease of adiposity and a resistance to obesity, demonstrating that myostatin can also impact on metabolism [14, 15]. In previous studies, we have shown that transgenic mice overexpressing Gasp-1 , a myostatin inhibitor, present a muscle hypertrophy without hyperplasia but no loss of fat mass unlike Mstn -/- mice [27, 31]. To explore in more details the role of Gasp-1 on energetic metabolism, we characterized young and old overexpressing Gasp-1 mice phenotypes in comparison to young and old WT mice.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations